STUDENTS RESPONSE TO THE READABILITY OF POGIL-BASED INTERACTIVE E-MODULE ON HEAT TOPIC - Irsalina, Fian Rifqi; Aviyanti, Lina; Iryanti, Mimin (Universitas Tanjungpura, 2026)
This study aimed to analyze the readability of a POGIL-based interactive e-module on heat for 12th-grade students. This study is urgent due to the abstract nature of heat concepts in physics and the increasing use of digital learning resources, which require instructional materials that are not only technologically advanced but also readable and pedagogically effective. The research employed a descriptive survey with a quantitative approach, collecting data via a questionnaire designed to assess three main aspects of the e-module: format, language, and content. A purposive sampling technique was employed, selecting 33 students who had previously studied the heat topic and had experience with e-modules. The data obtained were analyzed using a Likert scale to evaluate the effectiveness and practicality of the e-module. The results showed that the e-module received high ratings across all aspects, with an overall average score of 91.89%, categorizing it as “Very Practical.” The format aspect scored 90.06%, indicating that the e-module's design and structure were user-friendly and supported comprehension. The language aspect scored 92.73%, reflecting the clarity and simplicity of the language used. The content aspect scored 92.88%, indicating that the e-module effectively enhanced student engagement and understanding of the material. Overall, the study concludes that the e-module is a highly effective learning resource and is recommended for future instructional use.